Prosthetic and soft tissue considerations around anterior maxillary implants - Ricardo Palacios-Bañuelos; María José Zilleruelo-Pozo; Ludovica Oreglia; Lory Abrahamian; Alvaro Blasi (Elsevier, 2024)
This article provides a comprehensive exploration of critical factors influencing optimal outcomes in single-implant restorations in the anterior maxilla. The review delves into key considerations, including peri‑implant mucosal thickness, restorative materials, abutment height, emergence profile, 3-D implant position, and provisionalization timing. It highlights the importance of meticulous planning, from accurate diagnosis to precise implant positioning, while addressing advancements in computer-guided surgery. The present article emphasizes the complex interaction of surgical and prosthetic considerations and the need for a comprehensive approach to achieve success in implant dentistry.